Evaluation of Clayey Sand Subgrade Bearing Capacity Using Soaked and Unsoaked CBR Tests - Fina Afrilia Cahyaning; Heni Pujiastuti; Anwar Efendy; Ahmad Zarkasi (Universitas Medan Area, 2026)
This study evaluates the bearing capacity of highway subgrade through laboratory California Bearing Ratio (CBR) testing under soaked and unsoaked conditions. The research aims to determine the physical characteristics, compaction properties, and bearing capacity of clayey sand subgrade collected from Sepi Highway, West Lombok, Indonesia. Laboratory tests were conducted in accordance with the relevant Indonesian National Standards (SNI), including soil classification, Standard Proctor compaction, and CBR testing. The soil was classified as clayey sand (SC) based on the Unified Soil Classification System (USCS) and as A-2-7 according to the AASHTO classification system. The maximum dry density and optimum moisture content were 1.390 g/cm³ and 27.782%, respectively. The unsoaked CBR value reached 6.674%, whereas the soaked CBR value decreased significantly to 3.115%, indicating a substantial reduction in bearing capacity under saturated conditions. These findings demonstrate that water saturation is the primary factor reducing subgrade performance. Therefore, chemical stabilization, soil replacement, geotextile reinforcement, and improved drainage are recommended to enhance pavement stability and prolong highway service life.